The effect of dexmedetomidine on expression of neuronal nitric oxide synthase in spinal dorsal cord in a rat model with chronic neuropathic pain - Pang, Jun; Zhang, Suming; Kong, Ying; Wang, Zhe; Pei, Ruomeng; Zhuang, Ping; Wang, Xiaopeng (Arquivos de Neuro-Psiquiatria, 2023)
Background Neuropathic pain typically refers to the pain caused by somatosensory system injury or diseases, which is usually characterized by ambulatory pain, allodynia, and hyperalgesia. Nitric oxide produced by neuronal nitric oxide synthase (nNOS) in the spinal dorsal cord might serve a predominant role in regulating the algesia of neuropathic pain. The high efficacy and safety, as well as the plausible ability in providing comfort, entitle dexmedetomidine (DEX) to an effective anesthetic adjuvant. The aim of this study was to investigate the effect of DEX on the expression of nNOS in spinal dorsal cord in a rat model with chronic neuropathic pain.Methods Male Sprague Dawley (SD) rats were randomly assigned into three groups: sham operation group (sham), (of the sciatic nerve) operation (CCI) group, and dexmedetomidine (DEX) group. Chronic neuropathic pain models in the CCI and DEX groups were established by sciatic nerve ligation. The thermal withdrawal latency (TWL) was measured on day 1 before operation and on day 1, 3, 7 and 14 after operation. Six animals were sacrificed after TWL measurement on day 7, and 14 days after operation, in each group, the L4–6 segment of the spinal cords was extracted for determination of nNOS expression by immunohistochemistry.Results Compared with the sham group, the TWL threshold was significantly decreased and the expression of nNOS was up-regulated after operation in the CCI and DEX groups. Compared with the CCI grou[, the TWL threshold was significantly increased and the expression of nNOS was significantly down-regulated on day 7 and 14 days after operation in the DEX group.Conclusion Down-regulated nNOS in the spinal dorsal cord is involved in the attenuation of neuropathic pain by DEX.
Keywords: Dexmedetomidine; Neuralgia; Nitric Oxide Synthase Type I